PEMBERIAN EKSTRAK LIMBAH KEPALA UDANG SEBAGAI SUMBER PROTEIN PELENGKAP UNSUR GIZI PADA PENGOLAHAN KERUPUK - Rabiatul Adawyah; Findya Puspitasari (Fish Scientiae, 2019)
The goal of the research was to finding the best percentage of tapioca flour and shrimp extract in shrimp chips product. The percentage of tapioca flour and shrimp extract were control (A); 0.5 : 1 (B); 1 : 1 (C); 1.5 : 1 (D) with triple replicate. Proximate (protein) and oganoleptic were determined. From the result that 1 : 1 tapoica flour and shrimp extract was the best percentage in shrimp chips product.